2021
DOI: 10.4049/jimmunol.2100389
|View full text |Cite
|
Sign up to set email alerts
|

Role of Endosomal TLRs in Staphylococcus aureus Infection

Abstract: Identification of the receptors involved in innate immune recognition of Staphylococcus aureus, a major cause of morbidity and mortality in humans, is essential to develop alternative strategies to treat infections caused by antibiotic-resistant strains. In the current study, we examine the role of endosomal TLRs, which sense the presence of prokaryotic-type nucleic acids, in anti-staphylococcal host defenses using infection models involving genetically defective mice. Single deficiencies in TLR7, 9, or 13 res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…Absence of TLRs results in a decreased expression of proinflammatory cytokines, a reduced production of ROS, and an increased susceptibility to the S. aureus infection …”
Section: Discussionmentioning
confidence: 99%
“…Absence of TLRs results in a decreased expression of proinflammatory cytokines, a reduced production of ROS, and an increased susceptibility to the S. aureus infection …”
Section: Discussionmentioning
confidence: 99%
“…Specifically, TLR2 senses staphylococcal lipoproteins and TLR7, 9, and 13 recognizes staphylococcal nucleic acids. 62 At the same time, when MRSA infection occurs, its lipoprotein promotes TLR2/1 to participate in the production of IL-8. 63 Surprisingly, in our research, we found that phage cocktail supplemented with Ca 2+ and Zn 2+ could significantly increase the level of inflammatory factors in mice compared to the phage cocktail alone group, but did not lead to pathological changes of mouse organs ( Figure S5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Peritoneal lavage fluids were collected at the indicated times and analyzed for cytokine levels as previously described ( Mohammadi et al, 2016 ). For in vitro cytokine induction, bone marrow-derived macrophages were obtained from 8-week-old female mice and cultured in the presence of M-CSF as previously described ( Lentini et al, 2021 ). Macrophage cultures were then stimulated for 1 h with GBS grown to the late exponential phase at the indicated multiplicities of infection (MOI).…”
Section: Methodsmentioning
confidence: 99%
“…Macrophage cultures were then stimulated for 1 h with GBS grown to the late exponential phase at the indicated multiplicities of infection (MOI). Cultures were then treated with penicillin and gentamycin (100 IU and 50 μg/ml) to kill extracellular bacteria and supernatants were collected at 18 h after culture, as previously described ( Lentini et al, 2021 ). Cytokine levels were measured in peritoneal lavage fluid samples or culture supernatants by ELISA, using Mouse TNF-alpha DuoSet ELISA DY410, Mouse IL-1 beta/IL-1F2 DuoSet ELISA DY401, Mouse CXCL2/MIP-2 DuoSet ELISA DY452, Mouse CXCL1/KC DuoSet ELISA DY453 (R&D Systems).…”
Section: Methodsmentioning
confidence: 99%